Functional Modulation by Lactate of Myoglobin A MONOMERIC ALLOSTERIC HEMOPROTEIN - Bruno Giardina; Giampiero De Sanctis; Menico Rizzi; Paolo Ascenzi; Massimo Coletta; Maria Elisabetta Clementi (Journal of Biological Chemistry, 1996)
The effect of lactate on O2 binding properties of sperm whale and horse heart myoglobins (Mb) has been investigated at moderately acid pH (i.e. pH 6.5, a condition which may be achieved in vivo under a physical effort). Addition of lactate brings about a decrease of O2 affinity (i.e. an increase of P50) in sperm whale and horse heart myoglobins. Accordingly, lactate shows a different affinity for the deoxygenated and oxygenated form, behaving as a heterotropic modulator. The lactate effect on O2 affinity appears to differ for sperm whale and horse heart Mb, δlogP50 being ≈1.0 and ≈0.4, respectively. From the kinetic viewpoint, the variation of O2 affinity for both myoglobins can be attributed mainly to a decrease of the kinetic association rate constant for ligand binding.